Calorie restriction during gestation impacts maternal and offspring fecal microbiome in mice - Gilley, Stephanie P.; Ruebel, Meghan L.; Chintapalli, Sree V.; Wright, Clyde J.; Rozance, Paul J.; Shankar, Kartik (Frontiers in Endocrinology, 2024)
Background: Maternal undernutrition is the most common cause of fetal growth restriction (FGR) worldwide. FGR increases morbidity and mortality during infancy, as well as contributes to adultonset diseases including obesity and type 2 diabetes. The role of the maternal or offspring microbiome in growth outcomes following FGR is not well understood. Methods: FGR was induced by 30% maternal calorie restriction (CR) during the second half of gestation in C57BL/6 mice. Pup weights were obtained on day of life 0, 1, and 7 and ages 3, 4 and 16 weeks. Fecal pellets were collected from pregnant dams at gestational day 18.5 and from offspring at ages 3 and 4 weeks of age. Bacterial genomic DNA was used for amplification of the V4 variable region of the 16S rRNA gene. Multivariable associations between maternal CR and taxonomic abundance were assessed using the MaAsLin2 package. Associations between microbial taxa and offspring outcomes were performed using distance-based redundancy analysis and Pearson correlations. Results: FGR pups weighed about 20% less than controls. Beta but not alpha diversity differed between control and CR dam microbiomes. CR dams had lower relative abundance of Turicibacter, Flexispira, and Rikenella, and increased relative abundance of Parabacteroides and Prevotella. Control and FGR offspring microbiota differed by beta diversity at ages 3 and 4 weeks. At 3 weeks, FGR offspring had decreased relative abundance of Akkermansia and Sutterella and increased relative abundance of Anaerostipes and Paraprevotella. At 4 weeks, FGR animals had decreased relative abundance of Allobaculum, Sutterella, Bifidobacterium, and Lactobacillus, among others, and increased relative abundance of Turcibacter, Dorea, and Roseburia. Maternal Helicobacter abundance was positively associated with offspring weight. Akkermansia abundance at age 3 and 4 weeks was negatively associated with adult weight. Conclusions: We demonstrate gut microbial dysbiosis in pregnant dams and offspring at two timepoints following maternal calorie restriction. Additional research is needed to test for functional roles of the microbiome in offspring growth outcomes.